Penerapan GCG pada Bank Umum Syariah di Indonesia - Mu’arrif, Zul Ihsan (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
This study aims to see how far the application of GCG in Islamic banking in Indonesia. Because the Sharia Bank is a bank whose application of activities is different from conventional banks. Where one of the differences is the existence of a Sharia Supervisory Board that ensures the activities of banks based on sharia. Then a study of Islamic banks was conducted during 2014 until 2018. The method used was ANOVA and Panel Data Regression. The research results show that in the average test it was found that the application of GCG to Islamic banks was 'good', not yet able to reach the 'very good' level. In the panel test a number of points were found. First in general testing, the Board of Commissioners and Directors significantly influence GCG, while the Sharia Supervisory Board does not show significant results. In testing the fixed effect it was found that the Board of Directors and the Board of Commissioners were not significant indicating that both the Board of Directors and the Board of Commissioners had similarities in their various decisions. While the Sharia Supervisory Board showed significant results which meant that DPS had differences in their decisions. In the results of the time analysis it was found that the implementation of the GCG function did not change from time to time. It was found that the influence of individual banks was significant, while the influence of individual years was not significant.